Pengaruh Financial Attitude dan Financial Behavior Terhadap Literasi Keuangan Usaha Mikro Kecil (UMK) di Pasar Cicurug Kabupaten Sukabumi - Annisa Sirait, Bianca; Lasmana , Andy; Magdalena Melani , Maria Magdalena Melani (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
This research looks at financial attitudes and behavior towards financial literacy in MSEs. 85 traders were respondents. The research results show that a person's financial attitude partially has a positive and significant effect on the financial literacy of MSEs in Cicurug Market, and a person's financial attitude partially has a positive and significant effect on the financial literacy of MSEs in Cicurug Market. In addition, financial attitudes simultaneously have a positive and significant effect on the financial literacy of MSEs in Cicurug Market, with financial attitudes contributing more than attitudes. These results show how important it is to increase the financial knowledge of MSEs through good management of financial attitudes and behavior.